THE EFFECTS OF WORK–FAMILY CONFLICT AND FAMILY–WORK CONFLICT ON JOB EMBEDDEDNESS : THE MEDIATION OF EMOTIONAL EXHAUSTION - Rizana, Dani; Rohyani, Indah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
This study investigates the influence of Work–Family Conflict (WFC) and Family–Work Conflict (FWC) on Job Embeddedness, with Emotional Exhaustion serving as a mediating variable. A quantitative research approach was employed, using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. Data were collected through a survey of 300 courier expedition employees in Indonesia using a convenience sampling technique. The findings reveal that both WFC and FWC negatively and significantly affect Job Embeddedness, while simultaneously exerting a positive and significant impact on Emotional Exhaustion. Emotional Exhaustion, in turn, has a negative and significant effect on Job Embeddedness. The mediation analysis further confirms that Emotional Exhaustion significantly mediates the relationship between role conflicts and Job Embeddedness. These results highlight the detrimental effect of work-family conflicts on employees’ emotional well-being and their organizational attachment. The study underscores the importance of organizational strategies that promote work-life balance to sustain employee engagement and reduce turnover.